THE MANIFESTATIONS OF MILITARY GENDER ROLE ISSUE ON RIDLEY SCOTT’S G. I. JANE MOVIE - PUTRA, ABEDNEGO ANGGA JURIAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: gender discrimination, women in military, feminism, G.I. Jane movie. Gender discrimination threats the equality of women’s role. One of the causes of gender discrimination is patriarchal system in society. A movie entitled G.I. Jane reveals some causes and manifestations of gender discrimination in military.This research applies Feminism approach to analyze a movie entitled G.I. Jane. This study also applies the concept of gender role, women in military, and film studies.The result of the study reveals that gender discrimination results in many effects to women. In the movie G.I. Jane, the manifestations of gender role issues in military are caused by men domination, stereotypes toward women, and political aspect. The gender discrimination triggers many causes for women such as unequal treatments, job limitations, and controversial attitudes. Those effects cause chance limitation for women to participate in military sector.For future researchers, it is advisable to conduct further studies on the same movie but with different approaches. One of the examples is Semiotic approach. Semiotic approach can be used to analyze the signs and symbols that appear in the film, for example the differences of units in Army based on theiruniform or appearance depicted on G.I. Jane.